Dihydroactinidiolide from thermal degradation of β-carotene - Hazrulrizawati, Hamid; Suria, Kupan; M. M., Yusoff (Taylor & Francis, 2017)
The formation of dihydroactinidiolide by thermal degradation of β-carotene was studied. A comparison of yields of dihydroactinidiolide in commercial β-carotene and β-carotene derived from crude palm oil (CPO) was investigated. Thermal degradation of commercial β-carotene promoted the formation of dihydroactinidiolide with the highest yield, 61.21%. Thermal degradation of recovered β-carotene yielded 29.23% of dihydroactinidiolide. The lower recovery of β-carotene was due to the mixture of compounds in the extract. Further investigation indicated some other useful aroma compounds formed from this thermal degradation were β-ionone, 3-oxo-² -ionone and ² -cyclocitral.The outcome provided wide opportunities in utilizing crude palm oil (CPO) as natural source of beta-carotene to produce aroma compound.